Interventions to Empower Adults with Eating Disorders and Their Partners around the Transition to Parenthood. Issue 4 (4th December 2019) - Sadeh‐Sharvit, Shiri; Sacks, Madeline R.; Runfola, Cristin D.; Bulik, Cynthia M.; Lock, James D.
Abstract : The transition to parenthood is perceived as a stressful life event, when parents experience an immense change of their psychological focus and a reorientation of roles and responsibilities in the family system. This process may be even more challenging in the presence of a parental eating disorder history. This paper reviews the impact of parental eating disorders on the parents, the couple relationship, and their child during the perinatal period. A parental eating disorder is associated with more negative expectations of parental efficacy as well as specific difficulties in couple communication over the child's feeding, shape, and weight. Providers who better understand the effects of an eating disorder on parental functioning can more effectively intervene early on. We also present couple‐ or parent‐based, empirically supported interventions for adults with eating disorders and their partners in the prenatal and postnatal periods: Uniting Couples in the treatment of Anorexia Nervosa (UCAN) and Uniting couples In the Treatment of Eating disorders (UNITE) both enhance recovery from the eating disorder through a couple‐based intervention; the Maudsley Model of Treatment for Adults with Anorexia Nervosa (MANTRA) incorporates the support of partners, when appropriate; Parent‐Based Prevention (PBP) focuses on improving parental functioning and reducing risk of negative parental and child outcomes. Finally, we discuss the clinical implications of addressing parental eating disorders and encourage more research on these families. Abstract : La transición a la paternidad se percibe como una situación estresante de la vida, cuando los padres sufren un cambio inmenso en su foco de atención psicológico y una reorientación de los roles y las responsabilidades en el sistema familiar. Este proceso puede ser aun más difícil en presencia de antecedentes de trastornos alimentarios en los padres. Este artículo analiza el efecto de los trastornos alimentarios parentales en los padres, la relación de pareja y su hijo durante el periodo perinatal. Un trastorno alimentario parental está asociado con expectativas más negativas de la eficacia parental así como con dificultades específicas en la comunicación entre la pareja sobre la alimentación, la figura y el peso del niño. Los profesionales que mejor comprendan los efectos de un trastorno alimentario en el funcionamiento parental pueden intervenir más eficazmente en etapas tempranas. También presentamos intervenciones respaldadas empíricamente basadas en la pareja o en los padres para adultos con trastornos alimentarios y sus parejas en los periodos prenatales y posnatales: la "Unión de las parejas en el tratamiento de la anorexia nerviosa" (UCAN) y la "Unión de las parejas en el tratamiento de los trastornos alimentarios" (UNITE) mejoran la recuperación del trastorno alimentario mediante una intervención basada en la pareja; el modelo Maudsley de tratamiento para adultos con anorexia nerviosa (MANTRA) incorpora el apoyo de las parejas, cuando es adecuado; la prevención basada en los padres (PBP) se centra en mejorar el funcionamiento parental y en reducir el riesgo de consecuencias negativas para los padres y los niños. Finalmente, debatimos las implicancias clínicas de abordar los trastornos alimentarios parentales y de fomentar más investigaciones sobre estas familias. Abstract : 为人父母之后心理重心发生巨大变化，在家庭系统中的角色和责任也重新定位，身份的转变被认为是一个压力很大的生活事件。如果在亲历过自己父母的饮食失调史，该转换过程可能更具挑战性。本文回顾了围产期父母的进食障碍对父母，夫妻关系及其子女的影响。父母方面的的进食障碍与对父母效力的更多负面期望以及夫妻在孩子的喂养，体型和体重方面的交流中遇到的特殊困难有关。更好地了解饮食失调对父母功能的影响之后，提供者可以尽早更有效地进行干预。我们还针对有饮食障碍的成年人及其伴侣在产前和产后提供基于夫妇或父母的有实证支持的干预措施：联合夫妻治疗神经性厌食症（UCAN）和联合夫妻饮食失调（ UNITE）都通过基于夫妇的干预措施来增强从饮食失调中恢复的能力；Maudsley治疗成人神经性厌食症的模型（MANTRA）在适当时吸收了伴侣的支持；家长为基础的预防（PBP）的重点是改善父母的机能并降低父母和孩子的负面结果的风险。最后，我们讨论了解决父母饮食失调问题的临床意义，并鼓励针对这些家庭进行更多研究。